COVID-19 and Leisure: Directions for Policy Makers - Kantartzi, Ioanna Maria; Karlis, George (HAPSc Policy Briefs Series, 2020)
Epictetus, the Greek Stoic Philosopher, once said “Happiness and freedom begin with a clear understanding of one’s principle. Some things are within your control; and some things are not”. In adopting Epictetus quote for the current COVID-19 world, it has become more important than ever to realize that freedom and happiness can be intrinsic states that come from within the individual. Leisure, also an intrinsic state, is linked with freedom and happiness, and when leisure, freedom and happiness are experienced, a healthy lifestyle can be under your control and achieved. The current paper presents the importance of experiencing leisure, freedom and happiness for physical and mental health during the COVID-19 pandemic era. COVID-19 is not only political, social and economic challenge, but also a citizen’s well-being challenge. For this reason, three directions for policy making from the current and post COVID-19 era are presented: 1) the promotion of a healthy lifestyle, 2) individual and community activation and 3) empowering people.